Kemampuan Warga Belajar Lembaga Kursus Komputer Mendayagunakan Hasil Belajarnya - Muh. Yunus (Universitas Negeri Malang, 2016)
This research is aimed at finding out the factors affecting the ability of learners of computer course institutions (LKK) to apply what they have studied. The populations of the research are the instructors and learners of LKK. The samples are 41 LKKs, 41 instructors, and 188 LKK graduates. The data are collected by using a questionnaire and analyzed by using descriptive statistics and multiple regression techniques. The result of the analysis shows that the education program has the highest contribution to learners' achievement (27.02%), followed by the teaching intensity (25.09%). The lowest contibution is from the instructor's competence (18.29 %)